Walking the Line: Brokering Humanitarian Identities in Conflict Research. Issue 2 (3rd April 2019) - Lewis, Chloé; Banga, Alfred; Cimanuka, Ghislain; De Dieu Hategekimana, Jean; Lake, Milli; Pierotti, Rachael
ABSTRACT: Increasingly, academic research in conflict-affected contexts relies on support from humanitarian organizations. Humanitarian organizations constitute sites of study in and of themselves; they partner with academics to roll out surveys or randomized program interventions; and they frequently facilitate security, logistics and transportation for independent researchers. We use a research partnership between IRC, the World Bank, and academic researchers in the UK, the US and eastern DR Congo, to explore the effects of humanitarian affiliation on conflict field research. In investigating when, how and under what conditions humanitarian identities are adopted by researchers (and how these affiliations shape research dynamics) we identify three paradoxes. First, "wearing humanitarian clothes" to facilitate research logistics can both facilitate and constrain access. Second, humanitarian affiliations invoked by researchers to ensure security and protection in volatile research sites can undermine the "insider" status of local staff. Finally, working through humanitarian organizations allows local and international researchers to benefit from the protections and privileges afforded to humanitarian employees without providing any of the services on which privileged access rests. In this article, we map out decisions faced by local and international researchers concerning when to adopt and discard humanitarian identities, and the fraught logistical, ethical and methodological consequences of these decisions.